Development of the set of scales to assess the job satisfaction among physicians in Peru: validity and reliability assessment - David Villarreal-Zegarra; Roberto Torres-Puente; Ronald Castillo-Blanco; Baltica Cabieses; Luciana Bellido-Boza; Edward Mezones-Holguin (BMC, 2021)
Abstract Background To assess the validity and reliability of the set of scales (general professional activity, health services management, and working conditions) on the different areas of job satisfaction in Peruvian physicians based on the data from the National Survey of Satisfaction of Users in Health (ENSUSALUD). Method We carried out a psychometric study based on the secondary data analysis of Questionnaire 2 of ENSUSALUD-2016. Participants were selected from a two-stage stratified national probability representative sampling by political region. Validity was assessed by exploratory and confirmatory factor analyses, and measurement invariance analysis. We assessed the reliability using internal consistency coefficients (alpha and omega). The set of scales were composed of items related to three different areas of job satisfaction: 1) satisfaction with general professional activity, 2) satisfaction with the health services management, and 3) satisfaction with the working conditions of the health center. Results We included 2137 participants in the analysis. The general professional activity scale with six items (Comparative Fit Index, CFI = 0.946; Root Mean Square Error of Approximation, RMSEA = 0.071; Standardized Root Mean Square Residual, SRMR = 0.035), the health services management scale with eight items (CFI) = 0.972; RMSEA = 0.081; SRMR = 0.028), showed good measurement properties for the one-dimensional model. The working conditions scale with eight items for individual conditions and three items for infrastructural conditions (CFI = 0.914; RMSEA = 0.080; SRMR = 0.055) presented adequate measurement properties with a two-dimensional model. The invariance analysis showed that comparisons between sex, age, civil status, medical speciality, working in other institutions, work-related illness, chronic disease, and time working in the healthcare center. All scales had adequate internal consistency (ω and α between 0.70 and 0.90). Conclusions The set of scales has a solid factorial structure and measurement invariance, making it possible for group comparison. The study achieved stability in the scores as they showed adequate internal consistency coefficients. Based on our findings, these instruments are suitable for measuring job satisfaction among outpatient physicians throughout Peru, as our data is representative of the country level.